"Why would you not listen? It is like being given the winning lottery numbers and deciding not to take them": semi-structured interviews with post-acute myocardial infarction patients and their significant others exploring factors that influence participation in cardiac rehabilitation and long-term exercise training. Issue 17 (14th August 2022) - Thompson, Gareth; Wilson, Iseult M.; Davison, Gareth W.; Crawford, Jacqui; Hughes, Ciara M.
Abstract: Purpose: Despite the clinical benefits, coronary artery disease patient participation rates in cardiac rehabilitation (CR) and long-term exercise are poor. This study explored the factors related to participation in these interventions from the perspectives of post-acute myocardial infarction (AMI) patients and their significant others. Methods: Semi-structured interviews were performed with post-AMI patients (number ( n ) = 10) and their significant others ( n  = 10) following phase-III and phase-IV CR. Reflexive thematic analysis with an inductive orientation was utilised to identify themes within the dataset (ClinicalTrials.gov identifier: NCT03907293). Results: The overarching theme of the data was a perceived need to improve health, with the participants viewing health benefits as the principal motive for participating in CR and long-term exercise training. Three further themes were identified: motivation, extrinsic influences, and CR experience. These themes captured the underlying elements of the participants' decision to take part in CR and long-term exercise training for the purpose of health improvements. Conclusion: An AMI collectively impacts the attitudes and beliefs of patients and their significant others in relation to CR participation, long-term exercise, and health. The factors identified in this study may inform strategies to promote patient enrollment in CR and adherence to long-term exercise. IMPLICATIONS FOR REHABILITATION: Post-AMI patients and their significant others reported that health benefits were the primary motive for participating in CR and long-term exercise, with aspects related to motivation, extrinsic influences, and CR experience underpinning the decision. Healthcare professionals should supply information about health benefits during the CR referral process, with insights into the experiences of CR graduates potentially improving the strength of recommendation. CR facilitators may promote long-term exercise adherence by assisting patients with the identification of an enjoyable exercise modality. Healthcare professionals should include significant others in the CR referral process, which may enable these individuals to support the patients' decisions.